Governance for pro-poor urban development lessons from Ghana - Obeng-Odoom, Franklin (London Routledge, 2013)
The world development institutions commonly present 'urban governance' as an antidote to the so-called 'urbanisation of poverty' and 'parasitic urbanism' in Africa.
Includes bibliographical references (p. 204-252) and index.
Keywords: Urban policy--Ghana.